The Translation Notes Equivalency of Cultural Words in English – Indonesian “The Mafia Nanny” Webtoon Comic - Kurnia Fahma Zakia Darajat; Moh. Supardi; Tuty Handayani; Saefudin (Lakon : Jurnal Kajian Sastra dan Budaya, 2026)
This research aims to analyse the equivalence and the function of all the forms of translation notes that are used to translate cultural words in the “The Mafia Nanny” webtoon. Using a qualitative method through the lenses of Translation Notes and Cultural Words theory by Peter Newmark and the Meaning Equivalent theory by Nida and Taber, this research found a total of 17 cultural words that have been translated with the translation notes procedure, such as 13 data of footnotes and 4 data of body notes. This research also found that the translator mostly uses dynamic equivalence, which is 15 times, while rarely using formal equivalence, which is 2 times, in translating cultural words. Overall, this research demonstrates how the translation notes of cultural words in the webtoon act effectively as supplementary to maintaining the authenticity of the source language while maintaining the meaning equivalence with mostly dynamic equivalence.